ANALISIS KOMPARASI KINERJA KEUANGAN PADA PERBANKAN KONVENSIONAL BUKU IV DI INDONESIA SEBELUM DAN SESUDAH PANDEMI COVID-19 - Inka Tiono; Syahril Djaddang (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2021)
This research was conducted to analyze whether there are differences in financial performance in conventional banking BUKU IV before and after the COVID-19 pandemic based on capital ratio (Capital Adequency Ratio), earning asset quality ratio (Net Performing Loan), profitability ratio (Return on Asset & Return on Equity), efficiency ratio (BOPO: operational costs / operating income), and liquidity ratio (Loan / Deposit Ratio). Because of using saturated sampling technique, the objects that make up the population of this research are all used as research samples, that is seven banks that meet the criteria for BUKU IV including BCA, BNI, BRI, CIMB Niaga, Danamon, Mandiri, Panin. The results of this research shows that: ( 1) there is no difference in performance in conventional BUKU IV banking before and after the COVID-19 pandemic based on the CAR ratio; (2) there is a difference in performance in BUKU IV conventional banking before and after the COVID-19 pandemic based on the NPL ratio; (3) there is a difference in performance in conventional banking BUKU IV before and after the COVID-19 pandemic based on the ROA ratio; (4) there is a difference in performance in BUKU IV conventional banking before and after the COVID-19 pandemic based on the ROE ratio; (5) there is a difference in performance in BUKU IV conventional banking before and after the COVID-19 pandemic based on the BOPO ratio; and (6) there is a difference in performance in BUKU IV conventional banking before and after the COVID-19 pandemic based on the LDR ratio.